(untitled) (Journal of the College of Education for Women, 2019)
The islamic caliphate was against the Aarab who became Muslims andstayed in their desert and their companies didn’t share with the Muslims tospread Islam by Al-Jihad. The Quran attacked them in many verses exceptthe Aarab who accepted when the prophet called them for Al-Jihad.The Aarab in the ummayad period were in three categories :1. The aarab who lived in the desert ,the islamic society was very revengetowards them. The caliphate did not gave them Al-Ataa so they were inbad situation2. Those who lived in the country side . they were very trouble to thetrade.3. The third lived in the cities and worked in the trade, Dawawin and in theadministration.The Aarab of cities some of them associated with the caliphate,governer .they presented their activites and some of their committies. Thentheir religious features become clear so most of them had changed tobeleviors instead of only Muslims. The Arab who lived in the country side worked as guides of the tradecaravans or transporter the goods by the camels. The others were working asrobbers and plunders. Most of them shared with those who were against thecaliphate as away to declare their desier to the decentralization and revoltedagainst the caliphate in order to gain profitables.